The Moderation Effect of Religiosity on The Effect of Moral Equity to Auditor Ethical Behavior - Balqis, Anastania; Fanani, Zaenal (Jurnal Ilmiah Akuntansi dan Bisnis, 2021)
This research aimed to obtain the information and empirical evidence on the moderation effect of religiosity on the effect of moral equity to auditor ethical behavior. This research was conducted at the Public Accountant in East Java. This research uses primary data to obtain vital information from respondents using saturated sampling method. Respondents of this study were 102 auditors who work at the Public Accountant in East Java. This study uses a causality analysis Structural Equation Model (SEM) based component or variance or with the model name of Partial Least Square (PLS). Hypothesis testing will be done with the help of software WarpPLS 5.0. The results of this research indicate that religiosity is proved to have significant positive effect on the effect of moral equity to auditor ethical behavior. This finding can be useful for an auditor to be able to understand that there are several factors which can influence and strengthen ethical behavior.